Spatial variability in persistent organic pollutants and polycyclic aromatic hydrocarbons found in beach-stranded pellets along the coast of the state of São Paulo, southeastern Brazil - Taniguchi, Satie; Colabuono, Fernanda I.; Dias, Patrick S.; Oliveira, Renato; Fisner, Mara; Turra, Alexander; Izar, Gabriel M. [UNESP]; Abessa, Denis M.S. [UNESP]; Saha, Mahua; Hosoda, Junki; Yamashita, Rei; Takada, Hideshige; et al. (Elsevier, 2016)
High spatial variability in polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), organochlorine pesticides, such as DDTs, and polybrominated diphenylethers was observed in plastic pellets collected randomly from 41 beaches (15 cities) in 2010 from the coast of state of São Paulo, southeastern Brazil. The highest concentrations ranged, in ng g-1, from 192 to 13,708, 3.41 to 7554 and <0.11 to 840 for PAHs, PCBs and DDTs, respectively. Similar distribution pattern was presented, with lower concentrations on the relatively less urbanized and industrialized southern coast, and the highest values in the central portion of the coastline, which is affected by both waste disposal and large port and industrial complex. Additional samples were collected in this central area and PCB concentrations, in ng g-1, were much higher in 2012 (1569 to 10,504) than in 2009/2010 (173 to 309) and 2014 (411), which is likely related to leakages of the PCB commercial mixture.
Keywords: Brazil; Organochlorine pesticides; Pellets; Polychlorinated biphenyls; Polycyclic aromatic hydrocarbons; São Paulo